2019
DOI: 10.1136/bcr-2018-226745
|View full text |Cite
|
Sign up to set email alerts
|

Retained tooth in the nasal cavity: a rare cause of nasal congestion

Abstract: A 59-year-old man presented with unilateral nasal congestion and discharge. Clinical examination revealed a mass in the floor of the nasal cavity. Sinus CT indicated a retained tooth or a dermoid cyst. It was removed by endoscopic surgery. Histology confirmed the diagnosis of a retained tooth. At follow-up, the patient reported no nasal symptoms. A retained nasal tooth is rare, and the symptoms are variable. It can resemble other diseases such as chronic rhinosinusitis. Surgical removal is recommended to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
1
0
3
Order By: Relevance
“…La presencia de diastemas entre incisivos centrales, quistes de erupción, erupción ectópica de incisivos centrales permanentes, retraso de erupción dentaria o apiñamiento dentario, podría indicar la presencia de mesiodens (Hyun et al, 2009;Ata-Ali et al, 2014). Se han documentado casos de mesiodens que erupcionan o se encuentran adyacentes a la fosa nasal, los cuales pueden generar hiperplasia de la mucosa nasal, dolor facial, abscesos, cefaleas, epistaxis recurrentes, obstrucción nasal, congestión nasal, secreción purulenta, entre otras, sin embargo, su incidencia de aparición es escasa (Kirmeier et al, 2009;Moeller et al, 2019). A diferencia de los mesiodens de ubicación frecuente, aproximadamente el 60 % de los mesiodens adyacentes a fosa nasal presentan sintomatología.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…La presencia de diastemas entre incisivos centrales, quistes de erupción, erupción ectópica de incisivos centrales permanentes, retraso de erupción dentaria o apiñamiento dentario, podría indicar la presencia de mesiodens (Hyun et al, 2009;Ata-Ali et al, 2014). Se han documentado casos de mesiodens que erupcionan o se encuentran adyacentes a la fosa nasal, los cuales pueden generar hiperplasia de la mucosa nasal, dolor facial, abscesos, cefaleas, epistaxis recurrentes, obstrucción nasal, congestión nasal, secreción purulenta, entre otras, sin embargo, su incidencia de aparición es escasa (Kirmeier et al, 2009;Moeller et al, 2019). A diferencia de los mesiodens de ubicación frecuente, aproximadamente el 60 % de los mesiodens adyacentes a fosa nasal presentan sintomatología.…”
Section: Introductionunclassified
“…En casos donde el acceso quirúrgico intraoral se encuentra limitado, alternativas de tratamiento mínimamente invasivas como el abordaje endoscópico intranasal es una opción a considerar, el cual ha mostrado resultados postoperatorios bastante satisfactorios. sin embargo, su aplicación es relativamente difícil y con bastantes limitaciones (Indeewar & Dutt, 2019;Moeller et al, 2019).…”
Section: Introductionunclassified
“…Extra-oral ectopic teeth are rare, with intranasal incidence reported ranging from 0.1% to 1% in the general population 1. Published case series have demonstrated that a less invasive nasoendoscopic approach can be successful, but given the variation in position of ectopic teeth within the nasal cavity and paranasal sinuses, a conventional surgical approach is sometimes required 2.…”
Section: Introductionmentioning
confidence: 99%
“…Сверхкомплектные зубы в полости носа могут привести к заложенности носа, хронической ринореи и дефектам речи. Наиболее распространенный сверхкомплектный зуб, который выявляется по средней линии верхней челюсти, известен как мезиоденс [4][5][6][7][8] .…”
unclassified